2014
DOI: 10.1038/gim.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

PALB2 sequencing in Italian familial breast cancer cases reveals a high-risk mutation recurrent in the province of Bergamo

Abstract: Purpose: Monoallelic germ-line deleterious mutations of PALB2 (partner and localizer of BRCA2) are associated with breast cancer risk and have been found in several populations, with carrier frequencies of ~1−2%. Initially, these mutations were considered to have moderate penetrance, but accumulating evidence now indicates that they are associated with much higher risk. Methods:In this study, we sequenced the PALB2 coding regions unlinked to BRCA (breast cancer) genes in 575 probands from Italian breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
(45 reference statements)
1
23
1
1
Order By: Relevance
“…These two studies [2, 3] together identified the p.Leu939Trp mutation in 10/1741 (0.57 %) women with breast cancer and 8/1534 (0.52 %) unaffected controls, suggesting that this mutation is not associated with breast cancer risk. Further, we later published a third study corroborating this null finding [4] and have subsequently reported additional evidence that the p.Leu939Trp mutation is not associated with breast cancer risk, based on genotyping of 42,671 breast cancer cases and 42,164 controls (odds ratio = 1.05, 95 % confidence interval = 0.83–1.32, p value = 0.70) [5]. Finally, we observed that the p.Leu939Trp mutation does not disrupt the HR-mediated DNA repair activity of PALB2 (Fig.…”
Section: Textmentioning
confidence: 59%
“…These two studies [2, 3] together identified the p.Leu939Trp mutation in 10/1741 (0.57 %) women with breast cancer and 8/1534 (0.52 %) unaffected controls, suggesting that this mutation is not associated with breast cancer risk. Further, we later published a third study corroborating this null finding [4] and have subsequently reported additional evidence that the p.Leu939Trp mutation is not associated with breast cancer risk, based on genotyping of 42,671 breast cancer cases and 42,164 controls (odds ratio = 1.05, 95 % confidence interval = 0.83–1.32, p value = 0.70) [5]. Finally, we observed that the p.Leu939Trp mutation does not disrupt the HR-mediated DNA repair activity of PALB2 (Fig.…”
Section: Textmentioning
confidence: 59%
“…PALB2 mutations were previously identified through Sanger sequencing or targeted next generation sequencing ([4, 7]; Weitzel/Neuhausen personal communication). When available, relatives of PALB2 mutation carriers were genotyped for their family-specific mutations by Sanger sequencing using primers previously described [4, 8].…”
Section: Participants and Methodsmentioning
confidence: 99%
“…and it is ncluded on clinical multigene breast cancer panels. We had previously identified a recurrent mutation – the c.1027C>T (p.Gln343*) in Northern Italy; it was detected in 6 of 113 familial cases and 2 of 477 controls all from the Bergamo province [4]. A second PALB2 mutation, c.2167_2168delAT (p.Met723Valfs*21), has been identified multiple times in individuals from geographically diverse areas by independent research groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PALB2 , which is located on chromosome 16p12.1, is established as the third clinically important moderate-to-high penetrance breast cancer predisposition gene after BRCA1 and BRCA2 [2]. Many studies have reported the role of PALB2 polymorphisms in several loci with regard to breast cancer risk in the past decade, however with conflicting results [3,4,5,6]. Inconsistent conclusions may be due to small sample sizes in previous studies with inadequate statistical power for complex traits.…”
Section: Introductionmentioning
confidence: 99%